The Cost of Health Insurance and Entry into Entrepreneurship - Frank M. Fossen; Mobarak Hossain; Sankar Mukhopadhyay; Peter Toth (Institute of Labor Economics (IZA), 2021)
Unavailable or expensive health insurance may hinder the transition of individuals from paid employment to entrepreneurship. The literature argues that the guaranteed availability of health insurance introduced by the Affordable Care Act (ACA) of 2010 could reduce this barrier to entrepreneurship and thereby increase entrepreneurial activity. In this paper, we investigate how much the cost of health insurance when leaving paid employment—given availability of health insurance—matters for the decision to become an entrepreneur. We use individual-level data from the Current Population Survey (CPS-ASEC) combined with county-level panel data on health insurance costs in local Health Insurance Exchanges (HIX) introduced by the ACA to estimate county-treatment fixed-effects regressions. The results indicate that increasing the premium of the benchmark HIX plan by 100 per month decreases the annual probability of entry into self-employment by 0.25 percentage points, which corresponds to 18% of the average annual entry rate.
Keywords: I13; I11; J22; J23; L26; 330; entrepreneurship; health insurance; premium; deductible; MOOP